2020
DOI: 10.1111/ijcp.13700
|View full text |Cite
|
Sign up to set email alerts
|

Readmissions among patients with COVID‐19

Abstract: Background Hospital readmissions are associated with poor patient outcomes and increased health resource utilisation. The need to study readmission patterns is even bigger during a pandemic because the burden is further stretching the healthcare system. Methods We reviewed the initial hospitalisation and subsequent readmission for 19 patients with confirmed COVID‐19 in the largest statewide hospital network in Rhode Island, US, from March 1st through April 19th, 2020. We also compared the characteristics and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
125
5
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(149 citation statements)
references
References 25 publications
(51 reference statements)
15
125
5
4
Order By: Relevance
“…The findings also provide support for claims that older adults (3) and individuals with pre-existing health conditions (9-13) are more likely to experience ongoing COVID-19 complications requiring follow-up. Moreover, it was notable that this study's GP attendees had higher readmission rates than those observed among the general population in previous studies (24,25).…”
Section: Comparison With Existing Literaturecontrasting
confidence: 51%
See 1 more Smart Citation
“…The findings also provide support for claims that older adults (3) and individuals with pre-existing health conditions (9-13) are more likely to experience ongoing COVID-19 complications requiring follow-up. Moreover, it was notable that this study's GP attendees had higher readmission rates than those observed among the general population in previous studies (24,25).…”
Section: Comparison With Existing Literaturecontrasting
confidence: 51%
“…In Ireland, ICU rates are estimated between 1-2% (5), while a systematic review of international literature calculated a pooled ICU rate = 15.4%, with 14.9% (23). Research also suggests that COVID-GP ATTENDANCE POST COVID-19 4 19 hospital re-admission rates are low (24), with COVID-19 re-admissions most likely to occur among immunocompromised and co-morbid populations (24,25). Early, rather than later readmissions, are more associated with COVID-19 related illness, as opposed to illness arising from pre-existing health conditions (25).…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 , 5 The readmission rate of 5.2% observed in our study is within the range of other reports. 3 , 13 , 14 , 15 …”
Section: Discussionmentioning
confidence: 99%
“…Yet, few studies to date have focused on posthospitalization outcomes in COVID-19; and among these studies, only post-hospitalization outcomes obtained by electronic medical record system abstraction have been captured, raising concern for underestimation of adverse outcomes. [12][13][14][15][16][17][18][19][20] Therefore, the actual incidence of COVID-associated post-discharge return to the emergency room, re-hospitalization, and mortality remains unknown.…”
Section: Introductionmentioning
confidence: 99%